On Best Approximations in Hyperconvex Spaces - Reny George; Zoran D. Mitrović; Hassen Aydi (Journal of Function Spaces)
In this manuscript, we present further extensions of the best approximation theorem in hyperconvex spaces obtained by Khamsi.